You can't lead with your feet on the desk: building relationships, breaking down barriers, and delivering profits - Fuller, Edwin D., 1945- (John Wiley & Sons, 2011)
In You Can’t Lead with Your Feet on the Desk, the leader of Marriott International Lodging, Ed Fuller, delivers real-world advice on how to connect with, manage, and do business with people in any culture, including employees, suppliers, and customers who often have roots in other culture.